Classification of cardiorespiratory fitness using the six-minute walk test in adults: Comparison with cardiopulmonary exercise testing - Dourado, V. Z.; Nishiaka, R. K.; Simões, M. S.M.P.; Lauria, V. T.; Tanni, S. E.; Godoy, I.; Gagliardi, A. R.T. [UNESP]; Romiti, M. [UNESP]; Arantes, R. L. [UNESP] (Taylor & Francis, 2021)
Background: The six-minute walk test (6MWT) distance could facilitate the assessment of cardiorespiratory fitness (CRF) in clinical practice as recommended. We aimed to develop a CRF classification using the 6MWT distance in asymptomatic adults considering the treadmill maximum oxygen uptake (V˙O2max) as the gold standard method. Methods: We evaluated V˙O2max and 6MWT distance in 1295 asymptomatic participants aged 18–80 years (60% women). Age- and sex-related CRF was classified based on the percentiles as very low (<5th percentile), low (5th–25th percentile), regular (26th–50th percentile), good (51st–75th percentile), excellent (76th–95th percentile), and superior (>95th percentile) for both V˙O2max and 6MWT distance. We investigated the 6MWT distance cut-off (%pred.) with the highest sensitivity and specificity for identifying each V˙O2max classification. Results: V˙O2max declined by 8.7% per decade in both men and women. The 6MWT distance declined by 9.3% per decade in women and 9.5% in men. We formulated age- and sex-related classification tables for CRF using the 6MWT distance. Moreover, the 6MWT distance (%pred.) showed excellent ability to identify very low CRF (6MWT distance ≤ 96%; AUC = 0.819) and good ability to differentiate CRF as low (6MWT distance = 97%–103%; AUC = 0.735), excellent (6MWT distance = 107%–109%; AUC = 0.715), or superior (6MWT distance > 109%; AUC = 0.790). It was not possible to differentiate between participants with regular and good CRF. Conclusion: The CRF classification by the 6MWT distance is valid in comparison with V˙O2max, especially for identifying adults with low CRF. It could be useful in clinical practice for screening and monitoring the cardiorespiratory risk in adults.
Keywords: 6MWT; Cardiovascular risk; Reference values; V˙O2max; Walking